Kakeya Inequalities by Maximal Functions in Hardy Spaces - ZhuoRan Hu (Journal of Function Spaces, 2022)
In this paper, we will introduce and study several types of Kakeya inequalities by the maximal functions in Hardy spaces in ℝn, n≥2, and we could obtain several inequalities associated with the Kakeya inequalities. We will show that MδSα,βtfp≲p,n,φ,ε1/δ5n/r+2εfp, when fx∈Lpℝn and suppf^ξ⊆B0,1.